Chapter La politicizzazione della questione migratoria tra vecchi e nuovi attori - Bulli, Giorgia (Studi e saggi, 2021)
How do right wing populist parties politicize migration in different political, economic and social contexts? The chapter aims to provide an answer to this question by analyzing four parties: the Italian (Northern) League, the Spanish VOX, the German Alternative for Germany and the Austrian Freedom Party. Opposition to migration and negative reactions towards multicultural societies are recurrent arguments in the rhetoric of right-wing populist parties. The authors offer a multidimensional description of converging and diverging patterns of representation of migration in the four countries.